Supply Chain Integration and Organizational Resources and Capabilities: The Moderating Effect of Stakeholders’ Support - Frimpong, John Manso; Kuutoume, Jacob; Gyamfi, Christiana Abrafi (International Review of Management and Marketing, 2024)
This study investigates the moderating role of stakeholder support in the relationship between supply chain integration and organizational resources and capabilities. This study collected two hundred and five usable responses from top and senior managers of brewery companies and their key suppliers. Structural equation modelling was used to assess the hypothesized causal paths. The findings indicate that stakeholder support positively moderates the relationship between supply chain integration and organizational resources, as well as the relationship between organizational resources and organizational capabilities. The study has demonstrated that the effect of supply chain integration on organizational resources and capabilities is contingent on the direct and indirect support from both primary and secondary stakeholders in the supply chain. This study contributes to the literature on supply chain management by providing insights into the moderating role of stakeholder support in the relationship between supply chain integration and organizational resources and capabilities. The study highlights the importance of stakeholder support in building the necessary capabilities for a firm to provide competitive services to its customers.